Flood risk assessment of Kemang Area as a central business in South Jakarta - Supratman Maman; Kusuma M.S.B.; Cahyono M.; Kuntoro Arno Adi (E3S Web of Conferences, 2024)
This paper presents a flood risk assessment of Kemang area which around 80 Ha as central business at South Jakarta, DKI Jakarta, Indonesia. It is crucial to asses this area as it well-known as central business that has high damaged due to affected by flooding. The objective of this study to know the current level flood risk in the area and then how structural interventions through improving drainage pumps capacity with 2 m3/s contribute to the its level. The rational method, HEC-RAS 2D, and GIS have applied for methods flood risk analysis in two years return period of rainfall (138 mm/day). Flood risks calculated based on hazard index, vulnerability index and capacity index in scale of 20 RT (neighbourhood associations). As the result, flood risk map show that the Kemang area has 65 % highly risk of flooding, 10 % in moderate level and the rest is low level risk of flooding. The current planning of structural intervention not significant to reduce risk level. Therefore, it needs more actions to reduce the flood risk level through both structural and non-structural measures such as normalization of drainage system, policy, social and private engagement.